How residential compactness and attractiveness can be shaped by environmental amenities in an industrial city?. (August 2018) - Mondal, Biswajit; Das, Dipendra Nath
Highlights: Housing structural parameters play a major role in house purchase in the small towns. Temperature and healthy vegetation significantly associated in the central city. People perceptions and environmental amenities can also induce the residential spill-over. Zonal policy is a practice of market reorientation, not enough to build a compact city. Abstract: At a time when rapid urbanization and environmental degradation continue to be serious issues of concern, there is an escalating need to promote sustainable living across the world, with due emphasis on environmental amenities. The economic value of these amenities cannot be overlooked either, as they are inevitable in undertaking compact city plan. However, due to inadequate understanding of economic and aesthetic value of environmental amenities developers, decision-makers and policy makers ignored its importance, resulting in massive exploitation. This study conducted in the city of Ahmedabad in India, explores the significance of local environmental amenities and residential attractiveness to elicit an urban expansion pattern. The geographically weighted hedonic regression is employed in this research to estimate the value of local amenities and spatial clustering is used to examine the environment induced residential pattern. Outcome shows that in addition to structural attributes, local residents are willing to pay for LST, NDVI, air quality, and tree cover, in spite of these services being exceedingly location-specific. Besides, widespread residential spillover is observed in association with environmental amenities. These outcomes of the study could be substantially useful to understand the importance of environmental services and also be beneficial to commence a regional public policy.